Analysis of Working Capital Management in Automotive Industry Sector Listed in Indonesia Stock Exchange - Satriya Candra Bondan Prabowo; Rini Safitri (MEC-J (Management and Economics Journal), 2021)
This study aims to determine the analysis of working capital management in automotive industry sector listed on the Indonesia Stock Exchange. The object of the study consisted of 12 companies included in the automotive industry sector which were listed on the Indonesia Stock Exchange from 2014 to 2018. The results showed that the average collection period, inventory collection period, average payment period, and cash conversion cycle showed fluctuating results during the study period . The less time it takes for a company to collect receivables, the more liquid a company is. While the less time needed to convert raw materials into finished goods shows good results because the inventory will not be too long in the warehouse so that it will reduce costs. The average payment period is relative for each company. That's because every company has a debt agreement with a certain period. The less time needed by the company since the raw materials purchased are paid until the trade receivables from the sale are billed, the better for the company because the faster the time needed to turn money into goods and into cash back which will increase company profits.